Agonist D2-dopamine receptors reduces hemoconcentration in hyperstimulated women undergoing assisted reproduction - S V Fetisova; I E Korneeva; T U Ivaniec (IP Berlin A.V., 2014)
Background. Ovarian hyperstimulation syndrome (OHSS) results from increased vascular permeability (VP) caused by ovarian hypersecretion of vascular endothelial growth factor (VEGF), which activates its receptor-2. In animals, the dopamine receptor 2 agonist cabergoline (Cb2) inactivates VEGF receptor-2 and prevents increased VP.Objective. Our objective was to test whether Cb2 reduces hemoconcentration and prevents OHSS in humans.Materials and methods. Cb2 0,5 mg/d (n=65) or a placebo (n=63) was administered from the day of oocyte retrieval (Day 0) until the day of embryo transfer (Day 5). Hemoconcentration were identified markers, such as hematocrit, hemoglobin, red blood cell count, platelet count and indicators of the inflammatory response of leukocytes.Results. Hematocrit (p